Examining the Impact of Individual, Environmental, Organizational, and Cultural Factors on the Improvement of Human Resource Productivity in Private Banks in Mazandaran Province - Ramezani Burkhani, Nasser; Vardi, Seyedeh Shayeseteh; Mehrara, Asadollah (Management Strategies and Engineering Sciences, 2024)
Efforts to improve and effectively utilize various resources, such as labor, capital, and information, are the goals of all managers. This study aims to examine the impact of individual, environmental, organizational, and cultural factors on the improvement of human resource productivity in private banks. The present research is applied in terms of its purpose and, based on its approach, is quantitative and descriptive-survey in nature. Data collection methods include library and field studies. The sampling method used in this study is stratified random sampling. The data collection instrument is a researcher-made questionnaire, derived from the theoretical framework of the study. The validity of the researcher-made questionnaire was assessed through face, content, and construct validity, and its reliability was confirmed using composite reliability and Cronbach's alpha, which was greater than 0.7. The statistical population of this study includes 300 managers and deputies of state-owned banks in Mazandaran Province. Based on the Krejcie and Morgan table, 169 participants were selected as the sample. For data analysis, structural equation modeling was conducted using PLS software. The findings indicate that individual, cultural, organizational, and environmental factors, with path coefficients of 0.233, 0.260, 0.391, and 0.960, respectively, influence the improvement of human resource productivity.